2017
DOI: 10.1177/0032258x17740317
|View full text |Cite
|
Sign up to set email alerts
|

Change or be changed: Diagnosing the readiness to change in the Canadian police sector

Abstract: Concerns have emerged over the readiness of police agencies to adapt to change. To better understand why this might be the case, we used Lewin’s theory of change and an emic methodology to investigate the internal and external forces for and against change within this sector. Using a qualitative methodology we analysed the data from 103 interviews with key police and community stakeholders to identify the drivers and barriers to planned change. Examination of the resulting force field diagram revealed that: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…A recent study on Canadian police found that organizational readiness to change was relatively low, and members were likely to actively resist strategic change. Hence, to support change it is instrumental to understand these perceived barriers and reduce them (Duxbury, Bennell, Halinski, & Murphy, 2018). Research suggests that police employees in Canada are less satisfied with the opportunities for professional training, job autonomy, and career advancement available to them (Duxbury, Bennell, McIntyre, Murphy, & Caputo, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on Canadian police found that organizational readiness to change was relatively low, and members were likely to actively resist strategic change. Hence, to support change it is instrumental to understand these perceived barriers and reduce them (Duxbury, Bennell, Halinski, & Murphy, 2018). Research suggests that police employees in Canada are less satisfied with the opportunities for professional training, job autonomy, and career advancement available to them (Duxbury, Bennell, McIntyre, Murphy, & Caputo, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Knaak et al (2019) found that organizational structure in conjunction with cultural buy-in were necessary to change attitudes and behaviours toward mental illness and help-seeking. Police culture and leadership attitudes have been identified as significant barriers to meaningful organizational change (Duxbury et al , 2017). However, there is some evidence that the culture may be in flux, divided by officers who are ready for change and those who are not (Brown et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Police organizations are often called upon to change their structures to better align with the new realities of their policing environment and RJ represents one of these new realities (Duxbury et al, 2018). Public policy is understood to be much more complex than had been previously recognized, where the factors that influence policy implementation are more intricate, multifaceted, multileveled and can vary in time according to local context (Hudson et al, 2019).…”
Section: Issues With Policy Implementationmentioning
confidence: 99%
“…This gap is often due to too many stakeholders, each having their own interests and views that may or may not be in line with the policy mandate. The implementation process is made more difficult by being driven from the top-down and from outside the organization, moving slowly, with visible changes being too small, difficult, and risky (Duxbury et al, 2018), with change often being subject to organizational and cultural barriers (Alaid & Montemayor, 2012;Bellingham, 2000). Changes within police departments to policy or internal rules are often not enough; changes to police culture must be made for reforms to meet expectations.…”
Section: Issues With Policy Implementationmentioning
confidence: 99%
See 1 more Smart Citation